Explaining the accumulation of victimization in vulnerable children: Interpersonal violence among children traumatized by war and disaster in a children's home in Sri Lanka. (1st February 2022) - Rajan, Vathsalan; Neuner, Frank; Catani, Claudia
Abstract: Research in postconflict settings indicated that children's exposure to war and natural disaster is a significant predictor of experiencing violence within their families. However, it is unclear if this effect is driven by characteristics of traumatized children or their parents. To disentangle these different factors we conducted a survey in a children's home in Sri Lanka. A total of 146 institutionalized children (aged 8 to 17) were interviewed using standardized questionnaires administered by local senior counselors in order to assess children's exposure to mass trauma, family violence, and violence in the institution as well as their mental health. Linear regression analyses revealed that, controlling for potential confounds, previous exposure to civil war was a significant predictor of violence by guardians in the children's home. In addition, previous exposure to family violence was a significant predictor of violence by peers in the institutions. A mediation analysis showed that children's internalizing and externalizing behavior problems partly mediated the relationship between violence prior to the admission to the children's home and violence in the children's home. The findings of our study provide evidence for the assumption that the transmission of mass trauma into interpersonal violence can occur independently from parents through children's psychopathology.